UNDERGRADUATE STUDENTS’ PERCEPTIONS OF CAREER GUIDANCE PROGRAMS IN KAZAKHSTANI STATE SCHOOLS - Domayev, Adil (Nаzаrbауеv Unіvеrsіtу Grаduаtе Sсhооl оf Еduсаtіоn, 2023)
All high school students think about their future profession but not all of them can enter it. There are hundreds of professional fields and specializations but students need to choose only one. On top of that, new professions appear while some of the old professions lose their relevance. Choosing a future career is a difficult process for a young person, and while parents and relatives want to help, they usually do not have enough information and knowledge either. Career guidance is a process of helping people to choose their future careers, which can be done through psychological tests, personal consultations, among others...